Identifikasi Formalin pada Jajanan Siomay - Kahar, Fitriani; Rondonuwu, Ferawati (Poltekkes Kemenkes Semarang, 2019)
Formalin is a colorless solution and smells very strong, usually used as a preservative of dead bodies. Provision of formalin preservatives is prohibited on food, even food containing formaldehyde if consumed continuously will cause symptoms of poisoning, cancer (liver cancer) which is caused indirectly. The purpose of research on identifying formaldehyde in Siomay qualitatively is to determine whether there is formaldehyde in Siomay taken in Tamamaung Village. From the identification results, 4 out of 5 (80%) samples do not contain formalin preservatives, the benefits of research to protect the consumer community, especially Siomay fans to stay safe in consuming Siomay traded in Tamamaung Urban Village prove that there is awareness of traders in producing food especially Siomay is much favored by the community. So that the government or community leaders provide information to traders and entrepreneurs and consumers, especially the general public in Kelurahan Tamamaung about the dangers of using formalin preservatives, so that they do not use formalin as a food preservative.